Phase Distribution for Subcooled Flow Boiling in an Inclined Circular Tube - Wei Bao; JianJun Xu; TianZhou Xie; BingDe Chen; YanPing Huang; DianChuan Xing (International Journal of Photoenergy)
An experimental investigation of phase distribution for subcooled flow boiling in an inclined circular tube (i.d. 24 mm) was conducted in this paper. The local interfacial parameters were measured by a double-sensor optical fiber probe, and the measurements were performed on three different directions in the inclined tube cross section. The experiment shows that the phase distribution under the inclined condition is different from the phase distribution under the vertical condition. The profiles skewed highly for 90° and 45° direction in the tube cross section, whereas the profile was also symmetrical at 0° direction. These results can be explained by the fact that buoyancy caused the bubbles to move toward the top of the tube cross section under inclined condition. In addition, the typical distributions were also influenced by the inclination angles.